Saving primary energy consumption through exergy analysis of combine distillation and power plant / Alhassan Salami Tijani, Nazri Mohammed and Werner Witt - Tijani, Alhassan Salami; Mohammed, Nazri; Werner, Witt (Research Management Institute, 2012)
Industrial heat pumps are heat-recovery systems that allow the temperature of waste-heat stream to be increased to a higher, more efficient temperature. Consequently, heat pumps can improve energy efficiency in industrial processes as well as energy savings when conventional passive-heat recovery is not possible. In this paper, possible ways of saving energy in the chemical industry are considered, the objective is to reduce the primary energy (such as coal) consumption of power plant. Particularly the thermodynamic analyses of integrating backpressure turbine of a power plant with distillation units have been considered. Some practical examples such as conventional distillation unit and heat pump are used as a means of reducing primary energy consumption with tangible indications of energy savings. The heat pump distillation is operated via electrical power from the power plant. The exergy efficiency of the primary fuel is calculated for different operating range of the heat pump distillation. This is then compared with a conventional distillation unit that depends on saturated steam from a power plant as the source of energy. The results obtained show that heat pump distillation is an economic way to save energy if the temperature difference between the overhead and the bottom is small. Based on the result, the energy saved by the application of a heat pump distillation is improved compared to conventional distillation unit. Key words: Distillation units; Heat integration; Exergy/energy system modelling.